Pengaruh Penambahan Tepung Kedelai Terhadap Tingkat Kesukaan Dan Kandungan Protein Pada Bakso Daging Sapi - jajang hermana; Aaf Falahudin; Oki Imanudin (Tropical Livestock Science Journal, 2023)
The aim of this research is to analyze the dosage of using soy flour on the level of preference and protein content of beef meatballs and to obtain a formula for the optimum use of soy flour on the level of preference and protein content of beef meatballs. This research used a Completely Randomized Design (CRD) method with 5 treatments and 4 replications. The ratio of tapioca flour to soy flour for each treatment is respectively P0 (100% : 0%), P1 (75% : 25%), P2 (50% : 50%), P3 (25% : 75%) and P4 ( 0% : 100%). The data obtained were analyzed using analysis of variance (ANOVA). Meanwhile, the protein content uses a descriptive test and if the results of the anova test show a significant difference, continue with the Duncan test. The research results showed that as soy flour was added to beef meatballs, the level of liking for the aroma, texture and taste decreased. The addition of soy flour did not affect the level of preference for the color of the beef meatballs produced. Beef meatball protein with the addition of soy flour is between 16.15 – 23.31%. In conclusion, the best formulation is the addition of soybean flour to P1 with a reddish ash color, the level of liking is somewhat like it, the aroma does not have the smell of soybeans, the level of liking is very like it, the chewy texture is the liking level is somewhat like it and the taste has no taste of soybeans with the level of liking is somewhat like it.